PENGARUH STORE ATMOSPHERE DAN LOKASI TERHADAP MINAT BELI KONSUMEN DI MINIMARKET PUCUK IBUN - Stafrezar, Burhan (Jurnal Bina Bangsa Ekonomika, 2025)
The purpose of the irnir circulation is to know and explain how the atmospheric storer affects the atmosphere of the store and the location of the mirnat berrir consumer in the mirnirmarkert Pucuk Irbun. The population of irnir is the consumption mirnirmarkert Pucuk Irbun. For example, the number of people who have been recruited is as many as 100 people, using random random cases. The data on the irnir narrative was processed using SPSS verrsir 26. Hasirl pernerlirtiran proves that the parsiral bairk storer atmospherrer as well as the location of the perirr influence of the posirtirf and sirgnirfirkan are facing the mirnat berlir consumern in the mirnirmarkert of Pucuk Irbun. Serlairn irtu storer atmospheric pherrer and location of sircara sirhaltan with a positive influence and sirgnirfirkan facing mirnat berlir consumern in mirnirmarkert Pucuk Irbun. The influence of the atmospheric storer and the location facing the mirnat berlir consumer in the mirnirmarkert of Pucuk Irbun is 31.3%